Protective Layer and Current Collector Design for Interface Stabilization in Lithium-Metal Batteries - Dayoung Kim; Cheolhwan Song; Oh B. Chae (Batteries)
Recent advancements in lithium-metal-based battery technology have garnered significant attention, driven by the increasing demand for high-energy storage devices such as electric vehicles (EVs). Lithium (Li) metal has long been considered an ideal negative electrode due to its high theoretical specific capacity (3860 mAh g−1) and low redox potential. However, the commercialization of Li-metal batteries (LMBs) faces significant challenges, primarily related to the safety and cyclability of the negative electrodes. The formation of lithium dendrites and uneven solid electrolyte interphases, along with volumetric expansion during cycling, severely hinder the commercial viability of LMBs. Among the various strategies developed to overcome these challenges, the introduction of artificial protective layers and the structural engineering of current collectors have emerged as highly promising approaches. These techniques are critical for regulating Li deposition behavior, mitigating dendrite growth, and enhancing interfacial and mechanical stability. This review summarizes the current state of Li-negative electrodes and introduces methods of enhancing their performance using a protective layer and current collector design.